A new approach to real-time precise point-positioning timing with International GNSS Service real-time service products. (19th September 2019) - Ge, Yulong; Qin, WeiJin; Su, Ke; Yang, Xuhai; Ouyang, Mingjun; Zhou, Feng; Zhao, Xingwang
Abstract: Real-time precise timing with the precise point-positioning (PPP) technique is of great interest for scientists. However, real-time precise products are not aligned to a unified time scale. Hence, real-time precise products can only be utilized for time transfer not for timing. Furthermore, if the reference time changes frequently, the receiver clock offset cannot be modelled to further improve the accuracy of timing. In this work, we present a precise satellite timing approach using International GNSS Service (IGS) real-time service products, obtaining the difference between the local time of the user and UTC( k ) directly using a global navigation satellite systems (GNSS) receiver. This approach is based on three steps: (1) receiving real-time data streams and receiver observations connected to UTC( k ); (2) aligning the reference time of the new precise products to UTC( k ) by a PPP approach, with the new precise products then being broadcast via NTRIP (networked transport of RTCM via internet protocol); and (3) obtaining the difference between local time and UTC( k ) directly using a GNSS receiver, which can be done by users anywhere on the Earth. Our numerical analyses clarify how our precise timing approach performs using IGS real-time service products. First, the standard deviation (STD) of the difference between the timing results and the receiver clock results released by the IGS final products is approximately 0.2 ns. The STD values of the difference are reduced by approximately 2.76%–25.66% using the between-epoch constraint model. Second, the frequency stability of the timing has a good consistency with the receiver clock offset from the IGS final products with regard to long-term stability, while the short-term stability of the timing with the between-epoch constraint model is better than that of IGS final products. Third, the real-time kinematic positioning accuracy obtained using the new products and CLK93 products is of a similar level when the clock offset is estimated with the white noise model. By using the new products, the positioning accuracy of the between-epoch constraint model is improved by 0.91%, 2.54% and 23.21% over the result without the clock model in three coordinate components.